Oral english communication difficulties and coping strategies of Diploma of Hotel Management Students at UiTM - Norafini Zulkurnain,; Sarjit Kaur, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
Being able to communicate effectively is a much sought after skill by employers in today’s globalised work contexts. This article examines the types of oral communication difficulties faced by Diploma level ESL learners. This study also analysed the types of communication strategies used by the students to cope with speaking and listening problems during English oral communication activities. With these research objectives, a questionnaire known as the Oral Communication Strategies Inventory (OCSI) was distributed to 100 Diploma of Hotel Management students at the UiTM branch campus in Penang. Following that, 16 students from the total population were interviewed and they also took part in a journal writing activity to explain the difficulties they encounter when engaging in English conversation with others. The results revealed that difficulties occurred due to learners’ lack of English language knowledge. It was also found that learners are keen to get involved in English oral communication activities and most of them negotiate meaning with the interlocutors to understand the intended messages. The implications of this study suggest that teachers should be more creative in constructing interactive learning experiences for their students and teach coping strategies as part of students’ repertories of oral communication skills.